Mamíferos de médio e grande porte do Parque Nacional das nascentes do Rio Parnaíba, Brasil - LIMA, Marcela Guimarães Moreira (Universidade Federal do Pará, 2013)
The Nascentes do Rio Parnaiba National Park is located at the convergence of the states of Piauí, Maranhão, Tocantins and Bahia. In order to evaluate the composition, richness, relative abundance, activity pattern of medium and largesized mammals of the Park, as well as the use of phytophysiognomies present at the study site by these species, an inventory was made using camera-trap, semi-structured interview and complementary sampling methods. It was registered a total of 37 species of mammals of medium and large size, distributed in 14 families and seven orders, 20 of which recorded by cameratraps, 16 by sightings and traces (footprints, feces and carcasses), and all through interviews with residents of the region. The estimator of the nonparametric richness Jackknife1 estimated 22 species for the Park (D.P. ± 1,41). Regarding phytophisiognomy, only gallery forest and cerrado sensu stricto showed a significant difference about the richness and relative abundance. Among the species recorded in the Park, the foxes Cerdocyon thous and Lycalopex vetulus were the most abundant, respectively. Concerning the use of habitat, only Cerdocyon thous and Mazama gouazoubira showed significant differences between the phytophisiognomy, the first being from general habit and recorded specially in areas of cerrado sensu stricto, and the second most frequent in areas of more dense vegetation (cerradão). With respect to the composition of species, the cluster analysis indicated the areas of cerrado sensu stricto and cerradão with close similarity, which is probably due to the closer floristic similarity between these environments. The analysis of regional composition showed that the Park presents greater similarity in species composition with the UCs located in the southern of Piauí state (E.E. of Uruçuí- Una and PARNA of Serra das Confusões) than with other areas of Cerrado.